Long-term Monitoring of Arterial Blood Pressure and Pulse: General Estimates of Readings and Their Relationships - Kuksa, Yuriy; Shibaev, Igor (Challenging Issues on Environment and Earth Science Vol. 4, 2021)
The research is based on long, regular observations of blood pressure and pulse - the heart rate (more than 18 years). The values of these readings are taken from the diary of self-control, which is kept by a patient, one of the authors of this publication, a man born in 1940. Such effective control over the patient's condition, implemented in our case, ensuring its normal vital activity, makes it possible to investigate the influence of external factors on the hemodynamics of the body and the manifestation of the marked temporal characteristics. A difference between the morning and evening series was noted. The characteristics of evening monitoring readings are more balanced. Spectral analysis allows for a more detailed analysis and comparison of the data. Seven-day component is clearly seen in evening series being modulated with three-year period for the pulse. The morning series are characterized by a “lunar” component with the ~27.35-day period. The absence of a weekly period in the morning readings indicates a rapid (moment of sleep) relaxation of the body from the rhythmic stress of the past day. The manifestation of the "lunar" response can be associated with an increased sensitivity of the body during and after the sleep. This work describes the patient's condition through the correlation of blood pressure and heart rate.